Major diseases of pregnancy and abortion in cows - L. V. Koreyba (Науковий вісник Львівського національного університету ветеринарної медицини та біотехнологій імені С.З. Ґжицького: Серія Ветеринарні науки)
The data from the literature of domestic and foreign authors indicates that reproductive pathology and infertility are often complex and multifactorial phenomena, in which veterinary specialists aim to determine the cause of its violation, as well as to prescribe effective treatment and propose preventive measures. Infertility is defined as a decrease in reproductive capacity in cows. Fertility losses in animals include all causes of pregnancy termination: embryo death, resorption, abortion at any stage of pregnancy, and stillbirth. According to various authors, the etiology is diverse and includes ineffective treatment, as well as abnormal anatomical development or function of the reproductive system. In addition, infection, invasion, and neoplasia may be involved. Miscarriage is considered a component of infertility but it is more specific in its etiology and pathogenesis. There are many potential causes of pregnancy termination, some of which are still not understood. The causes of abortion are divided into two main categories, namely, infectious and non-infectious; and the main diseases of pregnancy are divided into four groups: diseases that occur and develop in the maternal body and are related to pregnancy; diseases of the fetus and its membranes; diseases that are concomitant with pregnancy but not directly related to it; and extragenital pathology.